OR applications in public sector - Martinovič, Tomáš; Jablonský, Josef, 1955-; Suchánková, Tereza; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2012)
Operations research in public sector is overshadowed by business sector. However it deals with a substantial amount of problems which concern whole population. Although it is not presented so much, a lot of research was made in many areas of the public sector. This thesis provide some basic information about where the operations research can be used. Then some approaches and model system used in energy policy modeling are presented. Lastly the use of operations research in water quality management is illustrated on a basic model minimizing the cost of water treatment.
Vedoucí práce: Josef Jablonský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: matematické metody v ekonomii [obor bakal. práce]; bakalářské práce; bachelor's theses